ISOLATION AND CHARACTERIZATION OF NOVEL ANTIBIOTIC-PRODUCING ACTINOBACTERIA FROM THE RHIZOSPHERE OF INDONESIAN MANGROVE FORESTS - Triwahyuningsih, Nike; Mei, Chen; Schneider, Anna (Research of Scientia Naturalis, 2025)
The rise of antimicrobial resistance is a global health crisis, demanding the urgent discovery of novel antibiotics. Indonesian mangrove forests, as a unique and underexplored ecosystem, represent a promising frontier for bioprospecting novel microorganisms. The plant rhizosphere, a zone of intense microbial activity, is particularly rich in actinobacteria, a phylum renowned for its prolific production of bioactive secondary metabolites. This research aimed to isolate and characterize novel antibiotic-producing actinobacteria from the rhizosphere of Indonesian mangrove plants. Rhizosphere soil samples were collected, and actinobacteria were isolated using selective media. All isolates were screened for antimicrobial activity against Staphylococcus aureus, Escherichia coli, and Candida albicans via the agar well diffusion method. The most potent isolate was subsequently characterized using morphological, biochemical, and 16S rRNA gene sequencing. From 72 distinct isolates, 15 displayed antimicrobial activity. One isolate, designated MGR-17, demonstrated exceptionally potent, broad-spectrum inhibition against all tested pathogens. Based on polyphasic taxonomy, MGR-17 was identified as a potentially novel species of the genus Streptomyces. In conclusion, the rhizosphere of Indonesian mangroves is a fertile source for discovering unique actinobacteria capable of producing novel antibiotics, and the discovery of Streptomyces sp. MGR-17 underscores this potential.